Effect of baseline obesity and postoperative weight gain on the risk of channel revision following continent catheterizable urinary channel surgery. Issue 4 (August 2016) - Chan, Katherine H.; Szymanski, Konrad M.; Li, Xiaochun; Ofner, Susan; Flack, Chandra; Judge, Benjamin; Whittam, Benjamin; Misseri, Rosalia; Kaefer, Martin; Rink, Richard C.; Cain, Mark P.
Summary: Objective: Prior studies suggest that obese patients are at increased risk for complications following continent catheterizable urinary (CCU) channel surgery. We hypothesized that postoperative weight gain increases the risk of channel angulation, difficulty catheterizing, and possible channel perforation requiring subfascial revision. The purpose of this study was to evaluate whether baseline obesity or becoming overweight/obese postoperatively was associated with a greater risk of subfascial revision. Method: We reviewed retrospectively an institutional database of patients who underwent CCU channel surgery between the ages of ≥2 and <20 years from January 1990 to May 2013, excluding those with continent urinary reservoirs, continent vesicostomies, and those without body mass index (BMI) data. We collected data on patient/procedure characteristics, baseline/most recent BMI, and subfascial revision(s). We used Cox proportional hazard multivariable regression to assess the association of being overweight/obese at baseline (≥85% BMI) with time to first subfascial revision, and Fisher's exact test to compare rates of subfascial revision between those who became overweight/obese and those who did not. Results: Of the patients, 328/501 (65.5%) had baseline and post-baseline BMI data available: 53.4% male, 90.6% white, median age 7.4 years; median follow-up 76.4 months. Of the 328 patients, 38 (11.6%) had subfascial revisions. Baseline BMI data were available for 378 patients, and, of these, 130 (34.4%) were overweight/obese at baseline. Overweight/obese patients were more likely to undergo umbilical Monti (10% vs. 8.1%), non-umbilical spiral Monti (33.8% vs. 13.7%), and spiral umbilical Monti channels (13.8% vs. 7.3%) versus normal/underweight patients ( p  < 0.0001). From a multivariable Cox proportional hazard model controlling for age, BMI category, diagnosis, and ambulatory status, the hazard of subfascial revision for spiral umbilical Monti channels was 2.1× that of other channels (hazard ratio (HR) 2.1 [95% CI 1.2–3.8], p  = 0.01). Fifty-one out of 328 patients (15.6%) became overweight/obese postoperatively, with 7.8% having a subfascial revision vs. 12.3% of those whose weight category decreased or remained stable ( p  = 0.3) (Table 1). Conclusions: Patients who were overweight/obese at baseline were more likely to have channels constructed that are at the highest risk of subfascial revision. Patients who became overweight/obese postoperatively were not at greater risk of subfascial revision. Limitations include potential bias because of differential follow-up and inaccuracy of BMI percentile as a measurement of obesity.